2005
DOI: 10.1167/iovs.05-0820
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in Serum Vitamin A Arrest Accumulation of Toxic Retinal Fluorophores: A Potential Therapy for Treatment of Lipofuscin-Based Retinal Diseases

Abstract: These findings demonstrate the vitamin A-dependent nature of A2E biosynthesis and validate a novel therapeutic approach with potential to halt the accumulation of lipofuscin fluorophores in the eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
172
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(180 citation statements)
references
References 41 publications
5
172
0
3
Order By: Relevance
“…Because the photodegradative processes examined here could over time be responsible for cumulative damage to retina and Bruch's membrane, the present findings have implications with respect to development of therapeutics that address bisretinoid lipofuscin deposition in recessive Stargardt disease and AMD (55)(56)(57)(58)(59)(60) and justify efforts to protect the retina of STGD1 patients by reducing light exposure through the use of a black contact lens (61). Quantitative Fundus Autofluorescence.…”
Section: Discussionmentioning
confidence: 86%
“…Because the photodegradative processes examined here could over time be responsible for cumulative damage to retina and Bruch's membrane, the present findings have implications with respect to development of therapeutics that address bisretinoid lipofuscin deposition in recessive Stargardt disease and AMD (55)(56)(57)(58)(59)(60) and justify efforts to protect the retina of STGD1 patients by reducing light exposure through the use of a black contact lens (61). Quantitative Fundus Autofluorescence.…”
Section: Discussionmentioning
confidence: 86%
“…Several approaches under investigation involve limiting bisretinoid formation (42)(43)(44). A number of reports, including from the Age-Related Eye Disease Study, have also demonstrated a role for antioxidant intake in protecting against AMD progression (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…The excessive formation of these compounds in Stargardt macular degeneration, is considered to be the cause of a loss of RPE cells in recessive Stargardt disease, a blinding macular disorder of juvenile onset and probably also contributes to the etiology of age-related macular degeneration (AMD), a common cause of blindness in elderly people (Delori et al, 2001;Holz et al, 2001;Radu et al, 2005;Schmitz-Valckenberg et al, 2004;Scholl et al, 2004). Photochemical reactions initiated by excitation from the blue region of the spectrum may contribute to the adverse effects of lipofuscin accumulation.…”
Section: Introductionmentioning
confidence: 99%